Improving the efficiency of aerosolized insecticide testing against mosquitoes - Walter Fabricio Silva Martins; Emma Reid; Sean Tomlinson; George Evans; Jennie Gibson; Amy Guy; Martin Donnelly; David Weetman (Scientific Reports, 2023)
Abstract Developing robust and standardised approaches for testing mosquito populations against insecticides is vital for understanding the effectiveness of new active ingredients or formulations. Methods for testing mosquito susceptibility against contact insecticides or products, such as those delivered through public health programmes, are well-established and standardised. Nevertheless, approaches for testing volatile or aerosolized insecticides used in household products can be challenging to implement efficiently. We adapted WHO guidelines for household insecticides to develop a standardised and higher-throughput methodology for testing aerosolized products in a Peet Grady test chamber (PG-chamber) using caged mosquitoes and an efficient decontamination method. The new approach was validated using insecticide resistant and susceptible Aedes and Anopheles mosquito colonies. An added feature is the inclusion of cage-facing cameras to allow real-time quantification of knockdown following insecticide exposure. The wipe-based decontamination method was highly effective for removing pyrethroids' aerosolized oil-based residues from chamber surfaces, with < 2% mortality recorded for susceptible mosquitoes tested directly on the surfaces. There was no spatial heterogeneity for knockdown or mortality of caged mosquitoes within the PG chamber. The dual-cage approach we implement yields eight-times the throughput compared to a free-flight protocol, allows simultaneous testing of different mosquito strains and effectively discriminates susceptible and resistant mosquito colonies tested side-by-side.